Bottled up - Murray, Jaye. (New York : Speak, 2004)
A high school boy comes to terms with his drug addiction, life with an alcoholic father, and a younger brother who looks up to him.
600
"An ALA BBYA."
Keywords: Brothers -- Juvenile fiction; Problem families -- Juvenile fiction; Alcoholism -- Juvenile fiction; Drug abuse -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction